B. O. da educação: a visão dos policiais militares sobre a autoridade e a educação. - Brunetta, Antonio Alberto (Universidade Federal de São Carlos, 2003)
As the cases of violent occurrence rise in school premises, police tend to be present in the most relevant way in the inter-school relationship as to contribute with the reconstruction of the educational dynamics, mainly in aspects related to authority. In this context, some investigation is adequate about the roots of military formation and the experience of those law enforcement officers, who have been effectively working with preventive programs. Such programs are important in the current practices of the reconstruction of police affairs, however, some people still confuse aggressive acts with prevention. In the daily routine of these officers, who work with the Violence and Drug Prevention Educational Program (PROERD), a clear paradox of identity has been detected associated with the non-recognition, by members of the police department, and equally, by some school representatives, of their job. Both of the mentioned groups, police and educational staff, may bring a lack of positive credit to the officer on duty, whose responsibilities include working in connection with the school department. In this condition of exclusion there is a clear result of mutual respect among officers with activities in the PROERD and their pupils, which has strengthened the relationship between them and stimulated successful overcome of authority as a way of organization and discipline both in the school and education areas. Such considerations lead to the necessity of teachers and people involved with education to reflect about the image they produce about the officers, in search of getting over with the vision, which considers the police officers specially connected with repression, thus strengthen the rights of both the officers and the members of the community.
Keywords: Sociologia educacional; Autoridade; Polícia militar; Violência; Authority; Education; Police; Violence; CIENCIAS HUMANAS::EDUCACAO